Listening to sustainable bites: Assessing the influence of sound on sustainable food perceptions and behaviors using a data-driven approach (2025)
There is a growing recognition that sound plays a pivotal role in shaping consumer behavior, particularly in the context of food choices. Given that everyday food decisions significantly impact environmental and social outcomes, understanding how auditory cues can guide more sustainable consumption is both timely and necessary. This thesis explores how sound can be strategically integrated into consumer experiences to influence perceptions of sustainability and promote healthier and more responsible food consumption. The research summarized here investigates the potential of auditory cues, ranging from packaging interaction sounds to tailored music soundscapes, to serve as subtle yet effective nudges that support sustainable decision-making. I hypothesize that sound can modulate perceptual and affective perceptions through crossmodal and cognitive mechanisms, and that these influences can be predicted and enhanced using artificial intelligence (AI). Rather than focusing solely on direct taste-sound interactions, this work situates auditory cues within broader multisensory and conceptual contexts, including product sounds mitigating negative affective associations, voiceovers disclosing ethical product origins, music influencing olfactory freshness, and soundscapes designed to evoke abstract sustainability concepts. At the core of this thesis are empirical studies and machine learning models that integrate experimental psychology, consumer behavior, and music information retrieval (MIR). This transdisciplinary research applies sound-based interventions across domains linked to key Sustainable Development Goals (SDGs), with chapters addressing directly SDGs 3, 9, 12, and 16 promoting healthier consumption, design and technological innovation, and responsible and inclusive markets through multisensory strategies. Key findings demonstrate that packaging sounds can shape emotions and refreshment expectation in non-alcoholic beverages, that auditory disclosure of conflict identities can affect consumer support for post-conflict producers, and that carefully designed music tracks can enhance the perceived freshness of fragrances or reinforce environmental and social sustainability narratives. Beyond behavioral evidence, this research also introduces the first transformer-based deep-learning model capable of predicting flavor associations from instrumental music, powering a flavor-driven music recommendation system. These results collectively highlight the underexplored power of sound in sustainable consumption contexts and contribute novel methodologies to multisensory and sustainability marketing research. This thesis suggests that incorporating auditory cues into the design of food and beverage experiences can increase consumer engagement, support post-conflict integration, and bridge the intention-action gap in sustainable consumption. Furthermore, it offers insights for marketers, designers, engineers, entrepreneurs, and policymakers interested in leveraging sound for experiential sustainability, proposing future applications in e-commerce, branding, hospitality, and AI-driven personalization. Finally, the implications of using sound as a tool for emotional mediation and behavioral influence are discussed, along with ethical considerations and calls for further interdisciplinary research to optimize multisensory strategies in the pursuit of the SDGs.